How to improve customer service efficiency and their customer satisfaction of Rupali Bank LTD. Gabtoli Hat Branch - Fariha, Rishad (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2019.